A four-sided stele with a depiction of St George - Melkonyan, Husik (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
This work is an analysis of two of the three four-sided stelae erected on the eastern side of the Zorats Church (1331) in the village of Yeghegis, Vayots Dzor province, Armenia. The third stele has not been preserved. On the first stele are depicted a cross and St George, the pan-Christian saint. The inscription is directed to God and St George, beseeching them for aid. This contribution discusses the issues of the chronology of the stelae, as well as the individual who ordered their construction. As a result of these analyses, it can be concluded that they were erected at the beginning of the 9th century by Archbishop Soghomon I – patriarch of Syunik at the time.